Assessing information literacy among students of Quezon City Science High School - Rulloda, Venice A.; Dela Torre, Nathalie N. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study was conducted to determine the current information literacy level among students of Quezon City Science High School and identify the factors that affect their information literacy competency. It sought to find out whether students from different year levels have the same or different information literacy competencies, identify whether their curriculum, library instruction received, and frequency of library use affect their information literacy competency.
The respondents of the study were 281 students of Quezon City Science High School enrolled in the school year 2008-2009, determined using stratified random sampling. Survey questionnaires consisting of three parts, each part corresponding to an IFLA IL Competency Standard, was the research instrument for this study.
The study revealed the following major results: the respondents' curriculum has a significant effect on their ILCE scores. Respondents from the Regional Science High School curriculum have higher IL scores than respondents from the ESEP curriculum. The respondents' library training received also has significant effects on their ILCE scores for Standards 1 and 2. Students who received library training have higher information literacy competency in Standards 1 and 2 compared with students who haven't received library training. Library training however did not have a significant effect on Standard 3. The respondents' year level also has significant effects on their ILCE scores. It is noticed that senior students generally scored the lowest in the ILCE while the first-year respondents scored the highest in the exam. And finally, the respondents' frequency of library use has effects on their ILCE scores for Standards 2 and 3 but none to Standard 1. It is also noted that there is a significant difference among the three IFLA Information Literacy Standards. The students scored the highest in Standard 1 - Access. This is followed by Standard 3 - Use. The lowest score received is for Standard 2 - Evaluation. However, it is noticed that the mean scores of the respondents in the three standards are not passing scores. It may be inferred that Quezon City Science High School students lack the IL skills that they need to be independent lifelong learners.
It is recommended that an information literacy program be integrated into the curricula of Quezon City Science High School. The administration, faculty and librarian are also urged to persuade and instill in the students the value of independent study and research. It is also necessary to recognize the vital role of librarians in imparting IL competencies. Honing the IL competencies of the students through the collaboration of the faculty and the librarian is also encouraged.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Quezon City Science High School -- Students; Information literacy -- Philippines -- Quezon City